Characterization of T-cell Subpopulations in Patients with Chronic Rhinosinusitis with Nasal Polyposis. Issue 3 (October 2017) - Ickrath, Pascal; Kleinsasser, Norbert; Ding, Xin; Ginzkey, Christian; Beyersdorf, Niklas; Hagen, Rudolf; Kerkau, Thomas; Hackenberg, Stephan
Background: There is an ongoing discussion concerning the potential origins of chronic rhinosinusitis with nasal polyposis (CRSwNP). Objective: The aim of this study was to quantify subpopulations of T cells in peripheral blood and nasal polyps in CRSwNP to examine their influence on the etiology of this disease. Methods: Tissue and blood samples were collected from 11 patients who underwent nasal sinus surgery, and these samples were analyzed by multicolor flow cytometry. Results: There was a significantly lower frequency of CD4 + T-helper (Th) cells and a significantly higher frequency of CD8 + T cells among lymphocytes isolated from nasal polyps compared with peripheral blood mononuclear cells (PBMC). In both T-cell subpopulations, a shift mainly from naive T cells among peripheral blood lymphocytes toward an effector memory and terminally differentiated subtype predominance in nasal polyps was observed. Among CD4 + T cells, the frequencies of cluster of differentiation (CD) 45RA- Forkhead-Box-Protein P3high (FoxP3 high ) cytotoxic T-lymphocyte-associated Protein 4 high (CTLA-4 high ) activated regulatory T (Treg ) cells, and CD45RA- Forkhead-Box-Protein P3low (FoxP3 low ) memory T cells were significantly increased in nasal polyps compared with PBMC. Conclusion: In this study, we presented a detailed characterization of CD4 + and CD8 + T-cell subpopulations in patients with CRSwNP. CD8 + T cells were more prominent in nasal polyps than in CD4 + T cells. Both nasal CD8 + T cells and CD4 + T cells predominantly had an effector memory phenotype. Among CD4 + T cells, activated Treg cells were increased in nasal polyps compared with PBMC. The data point toward a local regulation of T-cell composition within the microenvironment of nasal polyps, which might be further exploited in the future to develop novel immunotherapeutic strategies.